The effect of IBL (inquiry-based learning) model on EFL students’ critical thinking skills - Kamaruddin, Abdul; Patmasari, Andi; Agussatriana; Whanchit, Wararat; Suriaman, Aminah; Nadrun (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This research was conducted to discover whether the implementation of the IBL (Inquiry-Based Learning) model can improve EFL students’ critical thinking skills and to what extent the IBL model influences their critical thinking skills. This research implemented an explanatory research design. The sample was the students of the English Education Study Program who were taking the subject of Writing in Professional Context at one of the public universities in Central Sulawesi. The instruments used to collect data were tests and interviews. The data that were obtained in this research were analyzed quantitatively and qualitatively. The results show that the implementation of the IBL model is effective in improving the EFL students’ critical thinking skills. This achievement has to be supported by the implementation of a proper inquiry-based learning model. By implementing the IBL model, there is an increase in EFL students’ critical thinking skills in six aspects: interpretation, analysis, inference, evaluation, explanation, and self-regulation.